Analisis Faktor-Faktor Yang Mempengaruhi Tingkat Kepercayaan Masyarakat terhadap Lembaga Keuangan Syariah - Muhammad Rijalus Sholihin (Ecobuss, 2020)
The development of Information Technology should make the company grow rapidly, including Islamic Financial Institutions, both in terms of receipt and distribution of funds, but in fact we can see that Islamic financial institutions still tend to be less developed compared to conventional financial institutions, this is caused by many factors, and therefore the purpose of this study is to find out whether human resources in Islamic financial institutions, namely employees and products offered, can affect the level of public trust in Islamic financial institutions either partially or simultaneously. This type of research is quantitative by using a questionnaire as a method of data collection and then tested by multiple linear regression analysis. From the results of the study showed that human resources or employees of LKS positively affected with a significant value of 0.003 while the products offered did not affect sharia financial institutions with a significant value of 0.440, while simultaneously these two independent variables had a positive effect with a significance value of 0.005.